A participação das mulheres na agroecologia - Souza, Wanessa Alves Pereira de (2014)
This study aims to visualize the work performed by women in agriculture. Part assumption that live in a society patriarchal, activities in the life of reproduction are considered less important by do not generate direct income. It has the objective of presenting the reality of rural women workers and the importance of his work for food security and agroecology. Thus verifying, the context of agrarian issues experienced by them; identifying women's access to public policies; confirming the work performed by them; by viewing their forms of agricultural production; and ascertaining conception of agroecology and feminism by women. To analyze this context was used the method of qualitative research. Within the agricultural universe, was only researched women, aiming to evidence their looks over the reality. The research shows that women are being impacted by the agribusiness model and that still find difficult to advance in production in their territories by the difficult access to public policies. Women's work within the production is directed to the subsistence of the family, not being recognized as an indirect source of income; the same is based on an ecologically-based production, generating a diversity of products that ensures the family food security. It is concluded that there is a difference of reality between women that are inserted or not in social organizations; that still facing the limitations caused by the sexual division of labor; and that their work makes a significant contribution in ensuring food security and in the construction of agroecology.